2020
DOI: 10.3389/fonc.2020.00355
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Lymph Node Resection in Ovarian Cancer: A Population-Based Study

Abstract: Objective: This study aimed at comprehensively investigating the survival impact of lymphadenectomy during primary surgery in ovarian cancer. Methods: Based on the surveillance, epidemiology, and end results registry (SEER) database, we included ovarian cancer patients with detailed information between 2010 and 2016. Cox regression was performed to select prognostic factors. We conducted propensity score-weighted survival analysis to balance baseline variables, and series of stratified analyses to control main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…This finding disagreed with Gockley et al, (2017) study in which 96% of total cases were high-grade ovarian carcinomas. Cheng et al, (2020) study revealed that only 38% of cases had grade 3 EOC. Paes et al, (2011) andEdrem et al, (2018) also showed that 41% of cases were grade 2.…”
Section: Discussionmentioning
confidence: 97%
“…This finding disagreed with Gockley et al, (2017) study in which 96% of total cases were high-grade ovarian carcinomas. Cheng et al, (2020) study revealed that only 38% of cases had grade 3 EOC. Paes et al, (2011) andEdrem et al, (2018) also showed that 41% of cases were grade 2.…”
Section: Discussionmentioning
confidence: 97%
“…Although the quality of lymphadenectomy has improved with the experience of surgeons and improvement of surgical techniques by years, lymphadenectomy is absolutely associated with increased risk of complications [4,6] and this leads to some concerns about performing or canceling this approach. However, lymphadenectomy is a part of EOC surgery and is particularly important in early stage EOC when compared to advanced stage disease [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, results from randomized controlled studies demonstrate that lymphadenectomy was not associated with improved OS (HR: 1.02; 95% CI: 0.85-1.22). Similarly, in a population-based study, Cheng et al [11] showed that lymphadenectomy did not have a significant survival benefit among 4360 patients with advanced-stage ovarian cancer (median OS: 44 months in no-lymphadenectomy group and 49 months in lymphadenectomy group, p = 0.055). In a meta-analysis involving 1607 patients by Lin et al [26], systematic lymphadenectomy in patients with ovarian cancer was not associated with longer OS (HR: 1.00; 95% CI: 0.94, 1.07; p = 0.90) or PFS (HR: 0.97; 95% CI: 0.87, 1.08; p = 0.62) when optimal cytoreduction was achieved.…”
Section: Pelvic and Paraaortic Lymphadenectomymentioning
confidence: 93%
“…Systematic pelvic and paraaortic lymphadenectomy is a major component of the surgical staging procedure in apparent stage I disease. On the contrary, in advanced stages, retrospective studies have indicated an improved survival in patients who underwent systematic lymphadenectomy; randomized controlled studies reported no better outcomes [9][10][11][12]. Recently, differently from previous studies, the LION study, which was a well-designed randomized controlled trial, did not report any survival advantage for systematic lymphadenectomy in patients without bulky lymphadenopathy [12].…”
Section: Introductionmentioning
confidence: 97%